A Development classification in a non-linear (developing) world - Sumner, Andy (2013)
Presents an analysis of 101 of the 139 low and middle-income countries (i.e. 72% of the targeted countries and, 95.3% of the population of the developing world. Excludes countries with less than one million inhabitants or those countries and territories with limited statistical information viz., Antigua and Barbuda, Dominica, Grenada, St. Kitts and Nevis, Saint Lucia, and St. Vincent and the Grenadines which fit into the first category.